Lightning hazard mitigation in Uganda - Mary, Ahurra Kulyaka; Gomes, Chandima; Gomes, Ashen; Wan Ahmad, Wan Fatinhamamah (2014)
This paper addresses a concurrent burning issue in Uganda; the mitigation of rapidly increasing lightning hazards in the country. By analyzing various economic, technical and social factors a feasible hazard mitigation module has been proposed. The module essentially needs government intervention for providing facilities and coordination of various contributors and stakeholders for channeling expertise and possible funding. Several lightning disaster mitigation strategies have been proposed whereas practicality and limitations of applying them in Uganda are discussed in detail. Proposed modules are applicable in many countries having similar socio-economic environment